Dancing in and out of the archive: Tórtola Valencia, 'mestressa i odalisca' of herself. Issue 2 (June 2019) - Caulfield, Carlota
Abstract : This article explores how the body of early twentieth-century dancer Carmen Tórtola Valencia captured the imagination of diverse audiences in the decades up to the declaration of the Second Spanish Republic, drawing on testimonies by her contemporaries and more recent attempts to explain the widespread fascination with this female star of mysterious origins. In contrast with readings that have until now associated her figure with the fetishization of the female body and the embodiment of fin-de-siècle anxiety about the presence of women in the public sphere, I will explore how her negotiation of diverse spaces, traditions, and discourses reveals a more active, critical, and transgressive agency in relation to the aesthetic and social norms of her time. Unlike feminist readings that have attempted either to appropriate her as a body of protest or to critique her collusion in the perpetuation of the centrality of the masculine gaze, my own investigations in and out of the archive reveal a figure characterized by often contradictory and ambivalent fragments that are difficult to reconstruct as a coherent whole.